Novel Study of Cyproheptadine Hydrochloride Precipitate Formed by Potassium hexacyanoferrate and Sodium nitroprusside using Atomic Force Microscopy - Turkey Al-Awadie, Nagam S.; Shakir Al-Hashimi, Issam M.A.; Ismael Al-saadi, Kefah H. (Iraqi Journal of Science, 2023)
Atomic Force Microscope is an efficient tool to study the topography of precipitate. A study using Continuous Flow Injection via the use of Ayah 6SX1-T-2D Solar cell CFI Analyser . It was found that Cyproheptadine –HCl form precipitates of different quality using a precipitating agent’s potassium hexacyanoferrate (III) and sodium nitroprusside. The formed precipitates are collected as they are formed in the usual sequence of forming the precipitate via the continuous flow .The precipitates are collected and dried under normal atmospheric pressure. The precipitates are subjected to atomic force microscope scanning to study the variation and differences of these precipitates relating them to the kind of response to both precipitates give as. The incident light (i.e. super snow white LED) was scanned and it reveals that is , it compose of three components blue ,green and red color . The obtained spectrum were measured as a percentage area ( percentage effect ) also different models were study for the incident light irradiation of the measuring cell followed by the study of the effect on the detector area and responses .Various details and theoretical representation were adopted and were taken in to account ,the nodules (grains) on the surface were assumed to be sphere . The probability of radiation of the nodules of the surface of precipitate as the blue color and green color with the red color were 56.73% of green color , 42.12% of blue color and 1.15% of red color effect on the surface of precipitate .Granulation cumulating distribution data for both precipitates were measured also grains (nodules ) diameter were taken to concentration .